Birdcatching in Sagada and other poems - Cimatu, Frank (Philippine writers series 2021, 2021)
"Poet-journalist Franklin Cimatu not only wrote a poem about ikik but also used it as a motif for this first collection of poems in English. He caught the poems that flew from the North: poems about his parents, the Marcoses, Cordilleran revolutionaries, Hawaiian sacadas from Candon, and artist-friends from Baguio.